Composite fireproof insulation board and preparation method thereof

Through the design of multi-layer composite structure and interface bonding layer, the interlayer bonding strength and stability of straw aerogel materials are improved, and the insufficient application of existing materials in long-term use and extreme environments is solved, and excellent insulation separation is achieved Thermal and fire resistance.

CN119239065AActive Publication Date: 2025-01-03ZHEJIANG JUJIN HVAC INTELLIGENT TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411360937.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-03
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

The existing straw aerogel composites have shortcomings in interlayer bonding strength and stability, which are difficult to meet the application needs of long-term use and extreme environments.

Method used

Using a multi-layer composite structure, including a modified straw aerogel layer, a modified ceramic fiber layer and a metal foil layer, and the interlayer bonding strength is enhanced through the interface bonding layer. The specific steps include the treatment of straw fibers and the ultrafine inorganic powder. The use of dispersed and composite crosslinking agents and the application of interfacial coupling agents form nanoporous structures and high hydrophobicity.

Benefits of technology

The excellent interlayer bonding strength, stability, thermal insulation and fire resistance of the composite fireproof insulation board are achieved, and the overall performance of the material is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a composite fireproof insulation board and a preparation method thereof. The composite fireproof insulation board comprises a modified straw aerogel layer, a modified ceramic fiber layer and a metal foil layer which are stacked in sequence, the modified straw aerogel layer is prepared from straw fibers, superfine inorganic powder and a composite cross-linking agent through a sol-gel method, the mass percent of the straw fibers is 60-80%, the mass percent of the superfine inorganic powder is 15-30%, and the mass percent of the composite cross-linking agent is 5-15%; the modified ceramic fiber layer is composed of ceramic fibers, an inorganic binder and a functional filler; a first interface bonding layer is arranged between the modified straw aerogel layer and the modified ceramic fiber layer, and the first interface bonding layer is composed of an inorganic binder, superfine inorganic powder and an interface coupling agent; a second interface bonding layer is arranged between the modified ceramic fiber layer and the metal foil layer and is a nano inorganic coating. The thermal-insulation fireproof door has excellent interlayer bonding strength, stability, thermal-insulation performance and fireproof performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite fireproof and heat-insulating material, in particular to a composite fireproof and heat-insulating board and a preparation method thereof, and belongs to the technical field of building materials. Background Art

[0002] As a key material for building energy conservation, thermal insulation materials play a vital role in reducing building energy consumption and improving living comfort. However, traditional thermal insulation materials such as polystyrene foam and polyurethane foam, although they have good thermal insulation performance, generally have safety hazards such as flammable and toxic gas release. On the other hand, inorganic thermal insulation materials such as rock wool and glass wool, although they have good fire resistance, have relatively poor thermal insulation effects, and the production process is energy-intensive and polluting.

[0003] In recent years, biomass-based aerogel materials have attracted widespread attention due to their excellent thermal insulation performance, low density and environmental protection characteristics, especially straw aerogel, which can not only effectively utilize agricultural waste, but also has good thermal insulation performance. However, single straw aerogel materials still face problems such as insufficient strength and limited fire resistance in practical applications.

[0004] In the prior art, there have been studies on combining straw aerogel with other materials to improve its comprehensive performance. However, these composite materials still have deficiencies in interlayer bonding strength and stability, and are difficult to meet the application requirements of long-term use and extreme environments. Summary of the invention

[0005] Based on the above background, the purpose of the present invention is to provide a composite fireproof insulation board to solve the problems of insufficient interlayer bonding strength and poor stability of straw aerogel composite materials in the prior art, while having excellent thermal insulation and fireproof properties.

[0006] Another object of the present invention is to provide a method for preparing a composite fireproof thermal insulation board.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] A composite fireproof heat-insulating board comprises a modified straw aerogel layer, a modified ceramic fiber layer and a metal foil layer stacked in sequence;

[0009] The modified straw aerogel layer is prepared from straw fibers, ultrafine inorganic powder and a composite crosslinking agent by a sol-gel method, wherein the mass percentage of the straw fibers is 60-80%, the mass percentage of the ultrafine inorganic powder is 15-30%, and the mass percentage of the composite crosslinking agent is 5-15%;

[0010] The modified ceramic fiber layer is composed of ceramic fibers, inorganic binders and functional fillers, wherein the mass percentage of the ceramic fibers is 60-75%, the mass percentage of the inorganic binders is 20-25%, and the mass percentage of the functional fillers is 5-15%;

[0011] The metal foil layer is aluminum foil or stainless steel foil;

[0012] A first interface bonding layer is provided between the modified straw aerogel layer and the modified ceramic fiber layer, wherein the first interface bonding layer is composed of an inorganic binder, ultrafine inorganic powder and an interface coupling agent;

[0013] A second interface bonding layer is provided between the modified ceramic fiber layer and the metal foil layer, and the second interface bonding layer is a nano inorganic coating.

[0014] Preferably, the ultrafine inorganic powder is two or more of nano silicon dioxide, nano aluminum oxide, nano titanium oxide, nano zirconium oxide, and nano calcium carbonate; the composite crosslinking agent is composed of an organic silicon crosslinking agent and an organic titanium crosslinking agent in a mass ratio of 2-8:1-5; the organic silicon crosslinking agent is one or more of methyltrimethoxysilane, ethyltriethoxysilane, and phenyltrimethoxysilane; and the organic titanium crosslinking agent is one or more of tetraisopropyl titanate and tetra-n-butyl titanate.

[0015] Preferably, the inorganic binder is water glass, potassium silicate or aluminum phosphate modified by a surfactant, the surfactant is one or more of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, and polyethylene glycol, the added amount of the surfactant is 0.5-2% of the mass of the inorganic binder, and the functional filler is one or more of expanded graphite, aluminum hydroxide, magnesium hydroxide, and montmorillonite.

[0016] Preferably, the nano inorganic coating is one or more of a nano silicon dioxide coating, a nano aluminum oxide coating, and a nano titanium oxide coating.

[0017] Preferably, the thickness of the modified straw aerogel layer is 15-35 mm, the thickness of the modified ceramic fiber layer is 8-18 mm, the thickness of the metal foil layer is 0.05-0.2 mm, the thickness of the first interface bonding layer is 0.5-2 mm, and the thickness of the second interface bonding layer is 0.1-0.5 mm.

[0018] Preferably, the density of the modified straw aerogel layer is 0.08-0.15 g / cm 3 , thermal conductivity is 0.015-0.025W / (m·K), compressive strength is 0.2-0.5MPa; density of the modified ceramic fiber layer is 0.2-0.4g / cm 3, thermal conductivity is 0.03-0.05W / (m·K), and compressive strength is 0.5-1.0MPa.

[0019] A method for preparing a composite fireproof insulation board, the method comprising the following steps:

[0020] The straw fiber is soaked in a sodium hydroxide solution with a mass fraction of 2-5%, heated to 60-80°C and soaked for 2-4 hours, ultrasonically treated for 30-60 minutes, filtered, placed in a cellulase solution with a mass fraction of 1-3%, enzymatically treated at 45-55°C for 4-8 hours, filtered and washed to neutrality, and then immersed in a silane coupling agent ethanol solution with a mass fraction of 1-3%, immersed at room temperature for 2-4 hours, washed and dried, and crushed to 80-180 mesh;

[0021] The treated straw fibers are dispersed in an ethanol-water mixed solvent with a volume ratio of 7:3-9:1, a predetermined amount of ultrafine inorganic powder is added, and ultrasonic dispersion is performed for 30-60 minutes; a composite crosslinking agent is added, and the mixture is stirred at 20-30°C for 3-5 hours, and then aged at 55-75°C for 16-28 hours; the obtained sol is poured into a mold, and placed in a 40-60°C environment for gelation for 36-48 hours; the gel is immersed in ethanol for solvent exchange 2-3 times, and then heated to 60-80°C for drying for 24-48 hours, and finally heated to 120-150°C for heat treatment for 2-4 hours to obtain a modified straw aerogel layer;

[0022] The ceramic fibers are dispersed in water, an inorganic binder and a functional filler are added, and the mixture is dispersed by high-speed shearing for 15-30 minutes; the mixed slurry is formed into a sheet, heated to 80-100°C and dried for 4-6 hours, and then heated to 200-250°C and heat-treated for 1-2 hours to obtain a modified ceramic fiber layer;

[0023] The inorganic binder, the ultrafine inorganic powder and the interface coupling agent are mixed in a mass ratio of 5-8:1-3:0.1-0.5, and ultrasonically dispersed for 20-40 minutes to obtain a first interface bonding layer slurry; the nano inorganic coating component is dispersed in a solvent, and ultrasonically treated for 30-60 minutes to obtain a second interface bonding layer slurry;

[0024] The first interface bonding layer slurry is evenly sprayed or scraped on the surface of the modified straw aerogel layer, and the modified ceramic fiber layer is covered on the modified straw aerogel layer; the second interface bonding layer slurry is evenly sprayed or scraped on the surface of the modified ceramic fiber layer, and the metal foil layer is covered on the modified ceramic fiber layer; the above multilayer structure is placed in a hot press, hot-pressed at 120-150° C. for 30-40 minutes at a pressure of 0.5-1.0 MPa, and then cooled to room temperature to obtain a composite fireproof insulation board.

[0025] Compared with the prior art, the present invention has the following advantages:

[0026] The composite fireproof thermal insulation board of the present invention has excellent interlayer bonding strength, stability, thermal insulation performance and fireproof performance through the multi-layer composite structure and the interface bonding enhancement effect of the interface bonding layer;

[0027] The preparation method of the composite fireproof thermal insulation board of the present invention enables the modified straw aerogel layer to have an enhanced nanoporous structure and higher hydrophobicity and durability than ordinary straw aerogel, and is combined with a modified ceramic fiber layer with good stability and good thermal insulation performance, and the interlayer bonding strength of the whole board is improved through two interface bonding layers, finally obtaining a composite fireproof thermal insulation board with excellent interlayer bonding strength, stability, thermal insulation performance and fireproof performance. DETAILED DESCRIPTION

[0028] The technical solution of the present invention is further described in detail below through specific embodiments. It should be understood that the implementation of the present invention is not limited to the following embodiments, and any form of modification and / or change made to the present invention will fall within the protection scope of the present invention.

[0029] In the present invention, unless otherwise specified, all parts and percentages are weight units, and the equipment and raw materials used can be purchased from the market or are commonly used in the art. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art. The components or equipment in the following embodiments, unless otherwise specified, are universal standard parts or components known to those skilled in the art, and their structures and principles are known to those skilled in the art through technical manuals or conventional experimental methods.

[0030] The invention discloses a composite fireproof heat-insulating board, which comprises a modified straw aerogel layer, a modified ceramic fiber layer and a metal foil layer which are stacked in sequence.

[0031] The modified straw aerogel layer is prepared from straw fiber, ultrafine inorganic powder and composite crosslinking agent by sol-gel method, wherein the mass percentage of straw fiber is 60-80%, the mass percentage of ultrafine inorganic powder is 15-30% and the mass percentage of composite crosslinking agent is 5-15%.

[0032] The modified ceramic fiber layer consists of ceramic fiber, inorganic binder and functional filler, wherein the mass percentage of the ceramic fiber is 60-75%, the mass percentage of the inorganic binder is 20-25%, and the mass percentage of the functional filler is 5-15%.

[0033] The metal foil layer is aluminum foil or stainless steel foil.

[0034] A first interface bonding layer is arranged between the modified straw aerogel layer and the modified ceramic fiber layer, and the first interface bonding layer is composed of an inorganic binder, ultrafine inorganic powder and an interface coupling agent.

[0035] A second interface bonding layer is arranged between the modified ceramic fiber layer and the metal foil layer, and the second interface bonding layer is a nano inorganic coating.

[0036] Specifically, the ultrafine inorganic powder is two or more of nano silicon dioxide, nano aluminum oxide, nano titanium oxide, nano zirconium oxide, and nano calcium carbonate; the composite crosslinking agent is composed of an organic silicon crosslinking agent and an organic titanium crosslinking agent in a mass ratio of 2-8:1-5; the organic silicon crosslinking agent is one or more of methyltrimethoxysilane, ethyltriethoxysilane, and phenyltrimethoxysilane; and the organic titanium crosslinking agent is one or more of tetraisopropyl titanate and tetra-n-butyl titanate.

[0037] Specifically, the inorganic binder is water glass, potassium silicate or aluminum phosphate modified by a surfactant, the surfactant is one or more of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, and polyethylene glycol, the added amount of the surfactant is 0.5-2% of the mass of the inorganic binder, and the functional filler is one or more of expanded graphite, aluminum hydroxide, magnesium hydroxide, and montmorillonite.

[0038] Specifically, the nano inorganic coating is one or more of a nano silicon dioxide coating, a nano aluminum oxide coating, and a nano titanium oxide coating.

[0039] Specifically, the thickness of the modified straw aerogel layer is 15-35 mm, the thickness of the modified ceramic fiber layer is 8-18 mm, the thickness of the metal foil layer is 0.05-0.2 mm, the thickness of the first interface bonding layer is 0.5-2 mm, and the thickness of the second interface bonding layer is 0.1-0.5 mm.

[0040] Specifically, the density of the modified straw aerogel layer is 0.08-0.15 g / cm 3 , thermal conductivity is 0.015-0.025W / (m·K), compressive strength is 0.2-0.5MPa; density of modified ceramic fiber layer is 0.2-0.4g / cm 3 , thermal conductivity is 0.03-0.05W / (m·K), and compressive strength is 0.5-1.0MPa.

[0041] The present invention also discloses a method for preparing a composite fireproof thermal insulation board, which comprises the following steps:

[0042] Preparation of modified straw aerogel layer:

[0043] The straw fiber is soaked in a sodium hydroxide solution with a mass fraction of 2-5%, heated to 60-80°C and soaked for 2-4 hours, ultrasonically treated for 30-60 minutes, filtered, placed in a cellulase solution with a mass fraction of 1-3%, enzymatically treated at 45-55°C for 4-8 hours, filtered and washed to neutrality, and then immersed in a silane coupling agent ethanol solution with a mass fraction of 1-3%, immersed at room temperature for 2-4 hours, washed and dried, and crushed to 80-180 mesh;

[0044] The treated straw fibers are dispersed in an ethanol-water mixed solvent with a volume ratio of 7:3-9:1, a predetermined amount of ultrafine inorganic powder is added, and ultrasonic dispersion is performed for 30-60 minutes; a composite cross-linking agent is added, and the mixture is stirred at 20-30°C for 3-5 hours, and then aged at 55-75°C for 16-28 hours; the obtained sol is poured into a mold and placed in a 40-60°C environment for gelation for 36-48 hours; the gel is immersed in ethanol for solvent exchange 2-3 times, and then heated to 60-80°C for drying for 24-48 hours, and finally heated to 120-150°C for heat treatment for 2-4 hours to obtain a modified straw aerogel layer.

[0045] The modified straw aerogel layer obtained by the above steps has an enhanced nanoporous structure and higher hydrophobicity and durability than ordinary straw aerogels. First, the immersion of straw fibers in sodium hydroxide solution dissolves part of the hemicellulose and lignin, and the ultrasonic treatment further disperses the fibers to increase the specific surface area. The cellulose in some amorphous areas is selectively degraded by cellulase treatment to create more microporous structures. After that, a stable three-dimensional network structure is formed through the sol-gel process to maintain the nano-scale porous characteristics. Second, the silane coupling agent treatment forms a hydrophobic layer on the fiber surface to improve the hydrophobicity of the material, and a predetermined amount of ultrafine inorganic powder is added during the sol-gel process to enhance the overall stability and durability of the material.

[0046] Preparation of modified ceramic fiber layer:

[0047] The ceramic fiber is dispersed in water, an inorganic binder and a functional filler are added, and the mixture is dispersed by high-speed shearing for 15-30 minutes; the mixed slurry is formed into a sheet, heated to 80-100° C. and dried for 4-6 hours, and then heated to 200-250° C. and heat-treated for 1-2 hours to obtain a modified ceramic fiber layer.

[0048] The addition of inorganic binder firmly connects the ceramic fibers, and the functional filler significantly improves the thermal insulation performance of the material. After heat treatment at 200-250℃, it not only promotes the curing of the inorganic binder, but also triggers the phase change of the functional filler, resulting in the formation of a more stable high-temperature phase in the material, thereby improving the heat resistance of the material.

[0049] Preparation of the first interface bonding layer slurry and the second interface bonding layer slurry:

[0050] The inorganic binder, ultrafine inorganic powder and interface coupling agent are mixed in a mass ratio of 5-8:1-3:0.1-0.5, and ultrasonically dispersed for 20-40 minutes to obtain a first interface bonding layer slurry; the nano inorganic coating component is dispersed in a solvent and ultrasonically treated for 30-60 minutes to obtain a second interface bonding layer slurry.

[0051] Preparation of composite fireproof insulation board:

[0052] The first interface bonding layer slurry is evenly sprayed or scraped on the surface of the modified straw aerogel layer, and the modified ceramic fiber layer is covered on the modified straw aerogel layer; the second interface bonding layer slurry is evenly sprayed or scraped on the surface of the modified ceramic fiber layer, and the metal foil layer is covered on the modified ceramic fiber layer; the above multilayer structure is placed in a hot press, hot-pressed at 120-150° C. for 30-40 minutes at a pressure of 0.5-1.0 MPa, and then cooled to room temperature to obtain a composite fireproof insulation board.

[0053] The following is a combination of multiple embodiments and comparative examples to further illustrate a composite fireproof insulation board and a preparation method thereof disclosed in the present invention.

[0054] Example 1

[0055] Preparation of modified straw aerogel layer:

[0056] The straw fiber was soaked in a 3% sodium hydroxide solution by mass, heated to 70°C and soaked for 3 hours, ultrasonically treated for 45 minutes, filtered, placed in a 2% cellulase solution by mass, enzymatically treated at 50°C for 6 hours, filtered and washed to neutrality, and then immersed in a 2% γ-aminopropyltriethoxysilane ethanol solution by mass, immersed at room temperature for 3 hours, washed and dried, and then crushed to 100 mesh.

[0057] The treated straw fibers were dispersed in an ethanol-water mixed solvent with a volume ratio of 8:2, and nano-silica and nano-alumina (mass ratio of 3:1) were added, and ultrasonic dispersion was performed for 45 minutes; a composite cross-linking agent (methyltrimethoxysilane and tetraisopropyl titanate, mass ratio of 5:2) was added, stirred at 25°C for 4 hours, and then aged at 65°C for 24 hours; the obtained sol was poured into a mold and placed in a 50°C environment for gelation for 42 hours; the gel was immersed in ethanol for solvent exchange 3 times, and then heated to 70°C for drying for 36 hours, and finally heated to 135°C for heat treatment for 3 hours to obtain a modified straw aerogel layer.

[0058] The mass percentage of the straw fiber is 70%, the mass percentage of the ultrafine inorganic powder is 22%, and the mass percentage of the composite cross-linking agent is 8%.

[0059] Preparation of modified ceramic fiber layer:

[0060] The ceramic fiber was dispersed in water, and an inorganic binder (water glass modified by 1% sodium dodecylbenzene sulfonate) and a functional filler (expanded graphite and aluminum hydroxide, mass ratio of 1:1) were added, and high-speed shearing and dispersion was performed for 20 minutes. The mixed slurry was formed into a sheet, heated to 90°C for 5 hours, and then heated to 225°C for 1.5 hours to obtain a modified ceramic fiber layer.

[0061] The mass percentage of the ceramic fiber is 68%, the mass percentage of the inorganic binder is 22%, and the mass percentage of the functional filler is 10%.

[0062] Preparation of interfacial bonding layer:

[0063] First interface bonding layer: water glass, nano-silica and γ-aminopropyltriethoxysilane were mixed in a mass ratio of 6.5:2:0.3, and ultrasonically dispersed for 30 minutes to obtain a first interface bonding layer slurry.

[0064] Second interface bonding layer: Nano-silicon dioxide is dispersed in an ethanol solvent and subjected to ultrasonic treatment for 45 minutes to obtain a second interface bonding layer slurry.

[0065] Preparation of composite fireproof insulation board:

[0066] The first interface bonding layer slurry is evenly sprayed on the surface of the modified straw aerogel layer, and the modified ceramic fiber layer is covered on the modified straw aerogel layer; the second interface bonding layer slurry is evenly sprayed on the surface of the modified ceramic fiber layer, and the aluminum foil is covered on the modified ceramic fiber layer; the above multilayer structure is placed in a hot press, hot-pressed at 135° C. for 35 minutes at a pressure of 0.75 MPa, and then cooled to room temperature to obtain a composite fireproof insulation board.

[0067] In the final composite fireproof insulation board, the thickness of the modified straw aerogel layer is 25 mm, the thickness of the modified ceramic fiber layer is 13 mm, the thickness of the aluminum foil layer is 0.1 mm, the thickness of the first interface bonding layer is 1 mm, and the thickness of the second interface bonding layer is 0.3 mm.

[0068] Example 2

[0069] The preparation method is the same as in Example 1, except that:

[0070] When preparing the modified straw aerogel layer, the straw fiber is immersed in a sodium hydroxide solution with a mass fraction of 4%. The ultrafine inorganic powder is nano-silicon dioxide and nano-titanium oxide (mass ratio is 2:1), and the composite cross-linking agent is ethyl triethoxysilane and tetra-n-butyl titanate (mass ratio is 4:1). The mass percentage of straw fiber is 75%, the mass percentage of ultrafine inorganic powder is 18%, and the mass percentage of composite cross-linking agent is 7%.

[0071] When preparing the ceramic fiber layer, the inorganic binder is potassium silicate modified with 1.5% sodium dodecyl sulfate, and the functional filler is magnesium hydroxide and montmorillonite (mass ratio is 2:1). The mass percentage of ceramic fiber is 65%, the mass percentage of inorganic binder is 24%, and the mass percentage of functional filler is 11%.

[0072] When preparing the first interface bonding layer, potassium silicate, nano-alumina and γ-aminopropyltriethoxysilane are mixed in a mass ratio of 7:1.5:0.2.

[0073] When preparing the second interface bonding layer, nano-aluminum oxide is dispersed in isopropanol.

[0074] Stainless steel foil was used as the metal foil layer, and the hot pressing temperature was 140°C and the pressure was 0.8 MPa.

[0075] In the final composite fireproof insulation board, the thickness of the modified straw aerogel layer is 30 mm, the thickness of the modified ceramic fiber layer is 15 mm, the thickness of the stainless steel foil layer is 0.15 mm, the thickness of the first interface bonding layer is 1.5 mm, and the thickness of the second interface bonding layer is 0.4 mm.

[0076] Example 3

[0077] The preparation method is the same as in Example 1, except that:

[0078] When preparing the modified straw aerogel layer, the straw fiber is immersed in a sodium hydroxide solution with a mass fraction of 2.5%. The ultrafine inorganic powder is nano-silicon dioxide, nano-alumina and nano-zirconium oxide (mass ratio is 2:1:1), and the composite cross-linking agent is phenyltrimethoxysilane and tetraisopropyl titanate (mass ratio is 3:1). The mass percentage of straw fiber is 65%, the mass percentage of ultrafine inorganic powder is 25%, and the mass percentage of composite cross-linking agent is 10%.

[0079] When preparing the ceramic fiber layer, the inorganic binder is aluminum phosphate modified with 0.8% polyethylene glycol, and the functional filler is expanded graphite and aluminum hydroxide (mass ratio is 1:2). The mass percentage of the ceramic fiber is 70%, the mass percentage of the inorganic binder is 21%, and the mass percentage of the functional filler is 9%.

[0080] When preparing the first interface bonding layer, aluminum phosphate, nano titanium oxide and silane coupling agent KH570 are mixed in a mass ratio of 5.5:2.5:0.4.

[0081] When preparing the second interface bonding layer, nano titanium oxide is dispersed in n-butanol.

[0082] The hot pressing temperature was 130°C and the pressure was 0.7 MPa.

[0083] In the final composite fireproof insulation board, the thickness of the modified straw aerogel layer is 20 mm, the thickness of the modified ceramic fiber layer is 10 mm, the thickness of the aluminum foil layer is 0.08 mm, the thickness of the first interface bonding layer is 0.8 mm, and the thickness of the second interface bonding layer is 0.2 mm.

[0084] Example 4

[0085] The preparation method is the same as in Example 1, except that:

[0086] When preparing the modified straw aerogel layer, the straw fiber is immersed in a sodium hydroxide solution with a mass fraction of 3.5%. The ultrafine inorganic powder is nano-silicon dioxide and nano-calcium carbonate (mass ratio is 1:1), and the composite cross-linking agent is methyltrimethoxysilane and tetra-n-butyl titanate (mass ratio is 6:1). The mass percentage of straw fiber is 72%, the mass percentage of ultrafine inorganic powder is 20%, and the mass percentage of composite cross-linking agent is 8%.

[0087] When preparing the ceramic fiber layer, the inorganic binder is water glass modified by 1.2% sodium dodecylbenzene sulfonate, and the functional filler is magnesium hydroxide and montmorillonite (mass ratio is 3:1). The mass percentage of ceramic fiber is 67%, the mass percentage of inorganic binder is 23%, and the mass percentage of functional filler is 10%.

[0088] When preparing the first interface bonding layer, water glass, nano calcium carbonate and silane coupling agent KH560 are mixed in a mass ratio of 6:2.5:0.25.

[0089] When preparing the second interface bonding layer, nano silicon dioxide and nano aluminum oxide (mass ratio is 1:1) are dispersed in ethanol.

[0090] Stainless steel foil was used as the metal foil layer, and the hot pressing temperature was 145°C and the pressure was 0.85 MPa.

[0091] In the final composite fireproof insulation board, the thickness of the modified straw aerogel layer is 28 mm, the thickness of the modified ceramic fiber layer is 12 mm, the thickness of the stainless steel foil layer is 0.12 mm, the thickness of the first interface bonding layer is 1.2 mm, and the thickness of the second interface bonding layer is 0.35 mm.

[0092] Example 5

[0093] The preparation method is the same as in Example 1, except that:

[0094] When preparing the modified straw aerogel layer, the straw fiber is immersed in a sodium hydroxide solution with a mass fraction of 4.5%. The ultrafine inorganic powder is nano-silicon dioxide, nano-alumina and nano-titanium oxide (mass ratio is 2:1:1), and the composite cross-linking agent is ethyl triethoxysilane and tetraisopropyl titanate (mass ratio is 7:2). The mass percentage of straw fiber is 68%, the mass percentage of ultrafine inorganic powder is 23%, and the mass percentage of composite cross-linking agent is 9%.

[0095] When preparing the ceramic fiber layer, the inorganic binder is potassium silicate modified with 1.8% sodium dodecyl sulfate, and the functional filler is expanded graphite, aluminum hydroxide and magnesium hydroxide (mass ratio is 1:1:1). The mass percentage of the ceramic fiber is 69%, the mass percentage of the inorganic binder is 20%, and the mass percentage of the functional filler is 11%.

[0096] When preparing the first interface bonding layer, potassium silicate, nano-alumina and silane coupling agent KH792 are mixed in a mass ratio of 7.5:1.8:0.35.

[0097] When preparing the second interface bonding layer, nano-aluminum oxide and nano-titanium oxide (mass ratio of 1:1) are dispersed in an ethanol-water mixed solvent (volume ratio of 4:1).

[0098] The hot pressing temperature was 138°C and the pressure was 0.78MPa.

[0099] In the final composite fireproof insulation board, the thickness of the modified straw aerogel layer is 32 mm, the thickness of the modified ceramic fiber layer is 16 mm, the thickness of the aluminum foil layer is 0.18 mm, the thickness of the first interface bonding layer is 1.8 mm, and the thickness of the second interface bonding layer is 0.45 mm.

[0100] Example 6

[0101] The preparation method is the same as in Example 1, except that:

[0102] When preparing the modified straw aerogel layer, the straw fiber is immersed in a sodium hydroxide solution with a mass fraction of 3.8%. The ultrafine inorganic powder is nano-silicon dioxide and nano-zirconium oxide (mass ratio is 4:1), and the composite cross-linking agent is phenyltrimethoxysilane and tetra-n-butyl titanate (mass ratio is 5:1). The mass percentage of straw fiber is 73%, the mass percentage of ultrafine inorganic powder is 19%, and the mass percentage of composite cross-linking agent is 8%.

[0103] When preparing the ceramic fiber layer, the inorganic binder is aluminum phosphate modified with 1% polyethylene glycol, and the functional filler is aluminum hydroxide and montmorillonite (mass ratio is 3:2). The mass percentage of the ceramic fiber is 71%, the mass percentage of the inorganic binder is 21%, and the mass percentage of the functional filler is 8%.

[0104] When preparing the first interface bonding layer, aluminum phosphate, nano zirconium oxide and silane coupling agent KH550 are mixed in a mass ratio of 6.8:2.2:0.28.

[0105] When preparing the second interface bonding layer, nano silicon dioxide and nano titanium oxide (mass ratio is 2:1) are dispersed in isopropanol.

[0106] Stainless steel foil was used as the metal foil layer, and the hot pressing temperature was 142°C and the pressure was 0.82 MPa.

[0107] In the final composite fireproof insulation board, the thickness of the modified straw aerogel layer is 22 mm, the thickness of the modified ceramic fiber layer is 11 mm, the thickness of the stainless steel foil layer is 0.14 mm, the thickness of the first interface bonding layer is 1.3 mm, and the thickness of the second interface bonding layer is 0.38 mm.

[0108] Example 7

[0109] The preparation method is the same as in Example 1, except that:

[0110] When preparing the modified straw aerogel layer, the straw fiber is immersed in a sodium hydroxide solution with a mass fraction of 3.2%. The ultrafine inorganic powder is nano-silicon dioxide, nano-alumina and nano-calcium carbonate (mass ratio is 3:1:1), and the composite cross-linking agent is methyltrimethoxysilane and tetraisopropyl titanate (mass ratio is 4:1). The mass percentage of straw fiber is 71%, the mass percentage of ultrafine inorganic powder is 21%, and the mass percentage of composite cross-linking agent is 8%.

[0111] When preparing the ceramic fiber layer, the inorganic binder is water glass modified by 1.5% sodium dodecylbenzene sulfonate, and the functional filler is expanded graphite, magnesium hydroxide and montmorillonite (mass ratio is 2:2:1). The mass percentage of ceramic fiber is 66%, the mass percentage of inorganic binder is 22%, and the mass percentage of functional filler is 12%.

[0112] When preparing the first interface bonding layer, water glass, nano-alumina and silane coupling agent KH570 are mixed in a mass ratio of 6.2:2.3:0.32.

[0113] When preparing the second interface bonding layer, nano silicon dioxide, nano aluminum oxide and nano titanium oxide (mass ratio of 2:1:1) are dispersed in an ethanol-water mixed solvent (volume ratio of 3:1).

[0114] The hot pressing temperature was 137°C and the pressure was 0.76 MPa.

[0115] In the final composite fireproof insulation board, the thickness of the modified straw aerogel layer is 27 mm, the thickness of the modified ceramic fiber layer is 14 mm, the thickness of the aluminum foil layer is 0.16 mm, the thickness of the first interface bonding layer is 1.6 mm, and the thickness of the second interface bonding layer is 0.42 mm.

[0116] Example 8

[0117] The preparation method is the same as in Example 1, except that:

[0118] When preparing the modified straw aerogel layer, the straw fiber is immersed in a sodium hydroxide solution with a mass fraction of 3.6%. The ultrafine inorganic powder is nano-silicon dioxide and nano-titanium oxide (mass ratio is 5:2), and the composite cross-linking agent is ethyl triethoxysilane and tetra-n-butyl titanate (mass ratio is 6:1). The mass percentage of straw fiber is 74%, the mass percentage of ultrafine inorganic powder is 18%, and the mass percentage of composite cross-linking agent is 8%.

[0119] When preparing the ceramic fiber layer, the inorganic binder is potassium silicate modified with 0.9% polyethylene glycol, and the functional filler is aluminum hydroxide and magnesium hydroxide (mass ratio is 1:1). The mass percentage of ceramic fiber is 72%, the mass percentage of inorganic binder is 19%, and the mass percentage of functional filler is 9%.

[0120] When preparing the first interface bonding layer, potassium silicate, nano-titanium oxide and KH560 are mixed in a mass ratio of 7.2:1.6:0.26.

[0121] When preparing the second interface bonding layer, nano silicon dioxide and nano zirconium oxide (mass ratio is 3:1) are dispersed in n-butanol.

[0122] Stainless steel foil was used as the metal foil layer, and the hot pressing temperature was 133°C and the pressure was 0.72 MPa.

[0123] In the final composite fireproof insulation board, the thickness of the modified straw aerogel layer is 24 mm, the thickness of the modified ceramic fiber layer is 12 mm, the thickness of the stainless steel foil layer is 0.13 mm, the thickness of the first interface bonding layer is 1.1 mm, and the thickness of the second interface bonding layer is 0.32 mm.

[0124] Comparative Example 1

[0125] The preparation method is the same as that of Example 1, except that no ultrafine inorganic powder is added.

[0126] Comparative Example 2

[0127] The preparation method is the same as that of Example 1, except that no composite cross-linking agent is added.

[0128] Comparative Example 3

[0129] The preparation method is the same as that of Example 1, except that no functional filler is added.

[0130] Comparative Example 4

[0131] The preparation method is the same as that of Example 1, except that the first interface bonding layer is not provided.

[0132] Comparative Example 5

[0133] The preparation method is the same as that of Example 1, except that no second interface bonding layer is provided.

[0134] Comparative Example 6

[0135] The preparation method is the same as that of Example 1, except that no metal foil layer is provided.

[0136] Comparative Example 7

[0137] Commercially available polystyrene foam board.

[0138] Comparative Example 8

[0139] Commercially available rock wool board.

[0140] Comparative Example 9

[0141] Commercially available mineral wool and cement-based refractory composite board.

[0142] Performance Testing

[0143] The composite fireproof insulation boards prepared in Examples 1-8 and Comparative Examples 1-6 were subjected to performance tests, and the test results are shown in the following table:

[0144]

[0145]

[0146] As can be seen from the above table, the composite fireproof insulation board prepared in Examples 1-8 of the present invention has excellent comprehensive performance, low thermal conductivity, high compressive strength and good fire resistance. In contrast, in the absence of any single key component or single key structure in Comparative Examples 1-6, the performance is significantly reduced. Specifically, Comparative Example 1 lacks ultrafine inorganic powder, resulting in loose material structure, increased thermal bridges, decreased mechanical strength and reduced fire resistance. The presence of ultrafine inorganic powder fills the microscopic pores of the material, reduces heat conduction, and contributes to the improvement of compressive strength and interlayer bonding strength. Comparative Example 2 lacks a composite crosslinking agent, which also leads to a loose structure and increased heat conduction inside the material. Comparative Example 3 lacks functional fillers, resulting in a decrease in the performance of the material in terms of fire resistance and mechanical strength. The interface bonding layer lacking in Comparative Examples 4 and 5 mainly leads to a decrease in the mechanical properties of the material, especially the interlayer bonding strength. Comparative Example 6 lacks a metal foil layer, which has little effect on the thermal conductivity of the material, but significantly reduces the fire resistance limit. This shows that there is a synergistic effect between the components and structures of the composite fireproof insulation board of the present invention.

[0147] The thermal conductivity of Examples 1-8 is between 0.017-0.020 W / (m·K), which is significantly better than all comparative examples, especially 40-60% lower than polystyrene foam board (Comparative Example 7), rock wool board (Comparative Example 8) and composite board of mineral wool and cement-based fire-resistant layer (Comparative Example 9). This shows that the composite fireproof insulation board of the present invention has excellent thermal insulation performance. The compressive strength of Examples 1-8 is between 0.40-0.45 MPa, which is significantly higher than all comparative examples. In particular, it is about 3 times higher than polystyrene foam board (Comparative Example 7), about 7 times higher than rock wool board (Comparative Example 8), and about 1 times higher than composite board of mineral wool and cement-based fire-resistant layer (Comparative Example 9). This shows that the composite fireproof insulation board of the present invention has excellent mechanical properties. The fire resistance limits of Examples 1-8 are all between 4.1-4.4 hours, which is better than or equivalent to most comparative examples. In particular, it is about 8 times higher than the polystyrene foam board (Comparative Example 7), equivalent to the rock wool board (Comparative Example 8), and about 15% higher than the composite board of mineral wool and cement-based fire-resistant layer (Comparative Example 9). This fully demonstrates that the composite fireproof insulation board of the present invention has excellent fireproof performance. The interlayer bonding strength of Examples 1-8 is between 0.14-0.16MPa, which is significantly higher than all comparative examples. In particular, it is about 3 times higher than the polystyrene foam board (Comparative Example 7), about 50 times higher than the rock wool board (Comparative Example 8), and about 2 times higher than the composite board of mineral wool and cement-based fire-resistant layer (Comparative Example 9). This shows that the composite fireproof insulation board of the present invention has better integrity and durability. The dimensional change rates of Examples 1-8 are all between 0.2-0.3%, which is better than or equivalent to most comparative examples, and in particular, significantly better than the polystyrene foam board (Comparative Example 7). This shows that the composite fireproof insulation board of the present invention is not easy to deform during use and has good dimensional stability.

[0148] The principles and implementation methods of the present invention are described in this article using specific examples. The description of the above embodiments is only used to help understand the method and core ideas of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A composite fireproof insulation board, characterized in that: The composite fireproof heat-insulating board comprises a modified straw aerogel layer, a modified ceramic fiber layer and a metal foil layer which are stacked in sequence; The modified straw aerogel layer is prepared from straw fibers, ultrafine inorganic powder and a composite crosslinking agent by a sol-gel method, wherein the mass percentage of the straw fibers is 60-80%, the mass percentage of the ultrafine inorganic powder is 15-30%, and the mass percentage of the composite crosslinking agent is 5-15%; The modified ceramic fiber layer is composed of ceramic fibers, inorganic binders and functional fillers, wherein the mass percentage of the ceramic fibers is 60-75%, the mass percentage of the inorganic binders is 20-25%, and the mass percentage of the functional fillers is 5-15%; The metal foil layer is aluminum foil or stainless steel foil; A first interface bonding layer is provided between the modified straw aerogel layer and the modified ceramic fiber layer, wherein the first interface bonding layer is composed of an inorganic binder, ultrafine inorganic powder and an interface coupling agent; A second interface bonding layer is provided between the modified ceramic fiber layer and the metal foil layer, and the second interface bonding layer is a nano inorganic coating.

2. A composite fireproof insulation board according to claim 1, characterized in that: The ultrafine inorganic powder is two or more of nano silicon dioxide, nano aluminum oxide, nano titanium oxide, nano zirconium oxide, and nano calcium carbonate; the composite crosslinking agent is composed of an organic silicon crosslinking agent and an organic titanium crosslinking agent in a mass ratio of 2-8:1-5; the organic silicon crosslinking agent is one or more of methyltrimethoxysilane, ethyltriethoxysilane, and phenyltrimethoxysilane; and the organic titanium crosslinking agent is one or more of tetraisopropyl titanate and tetra-n-butyl titanate.

3. The composite fireproof insulation board according to claim 1, characterized in that: The inorganic binder is water glass, potassium silicate or aluminum phosphate modified by a surfactant, the surfactant is one or more of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate and polyethylene glycol, the added amount of the surfactant is 0.5-2% of the mass of the inorganic binder, and the functional filler is one or more of expanded graphite, aluminum hydroxide, magnesium hydroxide and montmorillonite.

4. The composite fireproof insulation board according to claim 1, characterized in that: The nano inorganic coating is one or more of a nano silicon dioxide coating, a nano aluminum oxide coating, and a nano titanium oxide coating.

5. The composite fireproof insulation board according to claim 1, characterized in that: The thickness of the modified straw aerogel layer is 15-35 mm, the thickness of the modified ceramic fiber layer is 8-18 mm, the thickness of the metal foil layer is 0.05-0.2 mm, the thickness of the first interface bonding layer is 0.5-2 mm, and the thickness of the second interface bonding layer is 0.1-0.5 mm.

6. The composite fireproof insulation board according to claim 1, characterized in that: The density of the modified straw aerogel layer is 0.08-0.15 g / cm 3 , thermal conductivity is 0.015-0.025W / (m·K), compressive strength is 0.2-0.5MPa; density of the modified ceramic fiber layer is 0.2-0.4g / cm 3 , thermal conductivity is 0.03-0.05W / (m·K), and compressive strength is 0.5-1.0MPa.

7. A method for preparing a composite fireproof insulation board, characterized in that: The method comprises the following steps: The straw fiber is soaked in a sodium hydroxide solution with a mass fraction of 2-5%, heated to 60-80°C and soaked for 2-4 hours, ultrasonically treated for 30-60 minutes, filtered, placed in a cellulase solution with a mass fraction of 1-3%, enzymatically treated at 45-55°C for 4-8 hours, filtered and washed to neutrality, and then immersed in a silane coupling agent ethanol solution with a mass fraction of 1-3%, immersed at room temperature for 2-4 hours, washed and dried, and crushed to 80-180 mesh; The treated straw fibers are dispersed in an ethanol-water mixed solvent with a volume ratio of 7:3-9:1, a predetermined amount of ultrafine inorganic powder is added, and ultrasonic dispersion is performed for 30-60 minutes; a composite crosslinking agent is added, and the mixture is stirred at 20-30°C for 3-5 hours, and then aged at 55-75°C for 16-28 hours; the obtained sol is poured into a mold, and placed in a 40-60°C environment for gelation for 36-48 hours; the gel is immersed in ethanol for solvent exchange 2-3 times, and then heated to 60-80°C for drying for 24-48 hours, and finally heated to 120-150°C for heat treatment for 2-4 hours to obtain a modified straw aerogel layer; The ceramic fibers are dispersed in water, an inorganic binder and a functional filler are added, and the mixture is dispersed by high-speed shearing for 15-30 minutes; the mixed slurry is formed into a sheet, heated to 80-100°C and dried for 4-6 hours, and then heated to 200-250°C and heat-treated for 1-2 hours to obtain a modified ceramic fiber layer; The inorganic binder, the ultrafine inorganic powder and the interface coupling agent are mixed in a mass ratio of 5-8:1-3:0.1-0.5, and ultrasonically dispersed for 20-40 minutes to obtain a first interface bonding layer slurry; the nano inorganic coating component is dispersed in a solvent, and ultrasonically treated for 30-60 minutes to obtain a second interface bonding layer slurry; The first interface bonding layer slurry is evenly sprayed or scraped on the surface of the modified straw aerogel layer, and the modified ceramic fiber layer is covered on the modified straw aerogel layer; the second interface bonding layer slurry is evenly sprayed or scraped on the surface of the modified ceramic fiber layer, and the metal foil layer is covered on the modified ceramic fiber layer; the above multilayer structure is placed in a hot press, hot-pressed at 120-150° C. for 30-40 minutes at a pressure of 0.5-1.0 MPa, and then cooled to room temperature to obtain a composite fireproof insulation board.

Citation Information

Patent Citations

  • Nanometer multiple-layer composite thermal insulation material and preparation method thereof

    CN101799099A

  • Fireproof and flame-retarding type composite heat-insulation decorating plate for outer wall and preparation method of fireproof and flame-retarding type composite heat-insulation decorating plate

    CN102587607A

  • Composite insulation material and insulation method thereof

    CN104879612A

  • Silica aerogel composite fiber and preparation method thereof

    CN107190365A

  • High-temperature-resistant thermal insulation material and preparation method thereof

    CN111848106A